(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Language is dynamic, constantly evolving to reflect the needs, values, and experiences of its speakers. In this context, dictionaries hold a unique role—not only as reference tools but also as gatekeepers, influencers, and mirrors of linguistic change. Over time, the approach to compiling dictionaries has shifted, and today, dictionaries not only reflect changes in language but often play a role in shaping them. This article explores how dictionaries document language change, legitimize new vocabulary, and affect the pace and acceptance of linguistic innovation